2021
DOI: 10.1080/21655979.2021.1975980
|View full text |Cite
|
Sign up to set email alerts
|

Four specific biomarkers associated with the progression of glioblastoma multiforme in older adults identified using weighted gene co-expression network analysis

Abstract: Glioblastoma multiforme (GBM) is the most common primary intracranial malignancy in adults. Owing to individual tolerance and tumor heterogeneity, the therapy methods for young adults do not apply to older adults. The present study aimed to identify specific biomarkers for GBM in older adults using weighted gene co-expression network analysis (WGCNA). Gene expression profiles of older adults with GBM were downloaded from The Cancer Genome Atlas (TCGA) and set as a discovery cohort to construct WGCNA. Core gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“… 29 OPALIN refers to the oligodendrocytic myelin paranodal and inner loop protein gene, which was found to be significantly correlated with the KPS score of elderly GBM patients. 30 Moreover, downregulated GRIN1, KCNJ9, GABRA1, ATP2B3 , and SLC17A7 in Module 1 were also enriched in the GSEA pathway terms that were associated with impaired neurological function; the low expression of the abovementioned genes highly correlated with worse OS in patients with low-grade glioma. 31 In addition, D’Urso et al reported that downregulation of miR-155 expression restored GABRA1 expression, which makes GBM cells more vulnerable to GABRA1-mediated anti-proliferation signals.…”
Section: Discussionmentioning
confidence: 93%
“… 29 OPALIN refers to the oligodendrocytic myelin paranodal and inner loop protein gene, which was found to be significantly correlated with the KPS score of elderly GBM patients. 30 Moreover, downregulated GRIN1, KCNJ9, GABRA1, ATP2B3 , and SLC17A7 in Module 1 were also enriched in the GSEA pathway terms that were associated with impaired neurological function; the low expression of the abovementioned genes highly correlated with worse OS in patients with low-grade glioma. 31 In addition, D’Urso et al reported that downregulation of miR-155 expression restored GABRA1 expression, which makes GBM cells more vulnerable to GABRA1-mediated anti-proliferation signals.…”
Section: Discussionmentioning
confidence: 93%
“…To differentiate between cell types in the GBM microenvironment, immune and non-immune clusters were classified based on marker genes identified in previous studies ( 41 58 ). Genes such as C1QB ( 41 ), CD68 ( 42 ), CSF1R ( 43 ), PTPRC ( 44 ), C1QC ( 45 ), P2RY12 ( 46 ), CX3CR1 ( 47 ), CD163 ( 48 ), PTGS2 ( 49 ) and CD86 ( 50 ) were used to identify immune clusters; whereas genes AQP4 ( 51 ), PTPRZ1 ( 52 ), CLDN5 ( 53 ), CD34 ( 54 ), GFAP ( 55 ), FDGFRA ( 56 ), OLIG2 ( 57 ) and PLP1 ( 58 ) were used to identify non-immune clusters. Clusters 0, 2, 6, 14 and 15 were identified as immune cells, whereas clusters 1, 3, 4, 5, 7, 8, 9, 10, 11, 12 and 13 were identified as non-immune cells based on the average expression of PTPRC, as demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To differentiate between cell types in the GBM microenvironment, immune and non-immune clusters were classified based on marker genes identified in previous studies (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58). Genes such as C1QB (41), CD68 (42), CSF1R (43), PTPRC (44), C1QC (45), P2RY12 (46), CX3CR1 (47), CD163 (48), PTGS2 (49) and CD86 (50) were used to identify immune clusters; whereas genes AQP4 (51), PTPRZ1 (52), CLDN5 (53), CD34 (54), GFAP (55), FDGFRA (56), OLIG2 (57) and PLP1 (58) were used to identify non-immune clusters. Clusters 0, 2, 6, 14 and 15 were identified as immune cells, whereas clusters 1, 3, 4, 5, 7, 8, 9, 10, 11, 12 and 13 were identified as non-immune cells based on the average expression of PTPRC, as demonstrated in Fig.…”
Section: Ccna2 and Nek2 Are Co-expressed In Npc Subtypesmentioning
confidence: 99%
“…The essence of Gene Significance (GS) is the correlation between the genes within the module where it is located and the phenotype (our phenotype was selected as whether or not we had PD) [48]. Reviewing a large amount of literature, we found that, generally, a GS threshold between 0.2 and 0.5 is reasonable [53][54][55][56][57][58][59][60]. At the same time, we wanted to include as many genes as possible to see the relationship with ferroptosis, so for the GS threshold, we chose 0.2.…”
Section: Plos Onementioning
confidence: 99%